The Role of Gender Responsive Facilities and Infrastructure in Supporting Students' Learning Motivation: A Qualitative Study - Hannisa, Artisia; Wakhudin, Wakhudin (Jurnal VARIDIKA, 2026)
This study aims to describe the role of elementary schools in providing and managing gender responsive facilities and infrastructure to support students’ learning motivation. A descriptive qualitative approach was employed to explore the experiences, perceptions, and practices of six elementary schools, varying in location, type, and completeness of facilities. Data were collected through interviews with principals, teachers, and students, observations of school facilities, and document analysis, and analyzed using a qualitative interactive process. The findings reveal that schools strive to provide various facilities, including comfortable classrooms, separate toilets, health rooms, libraries, sports fields, and both digital and printed learning media that portray balanced representations of male and female figures. School policies and teachers’ awareness of gender equality are reflected in the planning, utilization, and supervision of facilities, thereby fostering a learning environment that values all students regardless of gender. Students reported positive experiences, feeling comfortable and safe, as well as motivated to actively participate in classroom learning and extracurricular activities. These findings highlight the importance of integrating gender equality values into the management of school facilities and infrastructure to create an inclusive, participatory, and enjoyable learning experience. The study also emphasizes that attention to comfort, safety, and equal access contributes to shaping students’ perceptions of a fair learning environment and supports the development of their intrinsic motivation.